Analisis Kinerja Reksa Dana Saham Syariah Menggunakan Metode Sharpe, Treynor, dan Jensen (Aplikasi Bibit Periode 2021-2023) - Siti Rossy Aida; Renea Shinta Aminda; Diah Yudhawati (Jurnal Ekonomi dan Bisnis Digital, 2024)
The digital economy has become a strategic phenomenon in global economic development, with online trading changing the world economy. Investment has become something that many people, especially investors, like. Because it functions as a place to get information and learn about investment. With technological advances, investors can easily make investments and obtain information via digital platforms. One financial technology that is easy to use is the Bibit application. The COVID-19 endemic era is experiencing a health, economic and financial crisis due to increasing inflation and high Consumer Price Index (CPI). This research aims to determine the performance of sharia share mutual funds sold by Bibit mutual fund agents for the 2021-2023 period. This research is descriptive quantitative research using samples of Sharia stock mutual fund products registered in the Bibit application. The analytical methods used are Sharpe, Treynor, and Jensen. The research results show that the TRIM Syariah Stock mutual fund has the maximum value using the Sharpe method with a Sharpe result of -1752.28. Through the Treynor method, the TRIM Syariah Stock mutual fund has the maximum value with a Treynor result of -60,970. Through the Jensen method, the maximum value is owned by the Mandiri Investa Atractive-Syariah Sharia stock mutual fund with a Jensen result of 51.1765.